Leaf Functional Traits of Two Species Affected by Nitrogen Addition Rate and Period Not Nitrogen Compound Type in a Meadow Grassland - Sun, Lu; Yang, Guojiao; Zhang, Yang; Qin, Siqi; Dong, Jibin; Cui, Yangzhe; Liu, Xiao; Zheng, Peiming; Wang, Renqing (Frontiers in Plant Science, 2022)
Plasticity of plant functional traits plays an important role in plant growth and survival under changing climate. However, knowledge about how leaf functional traits respond to the multi-level N addition rates, multiple N compound and duration of N application remains lacking. This study investigated the effects of 2-year and 7-year N addition on the leaf functional traits of Leymus chinensis and Thermopsis lanceolata in a meadow grassland. The results showed that the type of N compounds had no significant effect on leaf functional traits regardless of duration of N application. N addition significantly increased the leaf total N content (LN) and specific leaf area (SLA), and decreased the leaf total P content (LP) and leaf dry matter content (LDMC) of the two species. Compared with short-term N addition, long-term N addition increased LN, LP, SLA, and plant height, but decreased the LDMC. In addition, the traits of the two species were differentially responsive to N addition, LN and LP of T. lanceolata were consistently higher than those of L. chinensis. N addition would make L. chinensis and T. lanceolata tend to “quick investment-return” strategy. Our results provide more robust and comprehensive predictions of the effects of N deposition on leaf traits.